USING OF ACCELEROMETER IN REHABILITATION OF BRAIN DAMAGE PATIENTS WITH UPPER ARM PARESIS - Petra Sladkova; Pavlina Oborna; Olga Svestkova (European Scientific Journal, ESJ, 2014)
Rehabilitation of patients after brain damage is an interprofessional, complex, intensive, long-term process. Often, motor disorder post brain damage results in paresis and causes impairment of upper arm movement pattern. Movement ability of the upper arm is vital for self-sufficiency and activities of daily life. Special rehabilitation therapeutic techniques must involve the training of new activities including the mechanism of motor learning which is responsible for functional reorganization of the motor cortex regions, and the activation of reserve neurons for reparation. The aim of the study is to demonstrate that an accelerometer is a suitable instrument for objective monitoring of impairment of the upper arm movement pattern with biofeedback principles. Another aim of the study is to demonstrate if the FIM test and Jebsen-Taylor (JT) test are appropriate instruments for detecting changes of the upper extremity movement pattern after intensive interprofessional rehabilitation brain damage patients. Clinical study was undertaken with selected patients after brain damage with paresis. The patients attended a rehabilitation day care center for 4 weeks. The parameter of an all-day movement activity of the upper arm was detected by an accelerometer measurement. The FIM and JT tests were applied at the beginning and after 4 weeks during the final examination. The results confirmed that an accelerometer is a suitable instrument for detecting of the changes of upper arm movement activity. Analysis of the results confirmed that functional tests, the FIM test and JT test, are sensitive to changes of functional abilities of patients after brain damage.